MF59 adjuvant: the best insurance against influenza strain diversity. (April 2011) - O''Hagan, Derek T; Rappuoli, Rino; De Gregorio, Ennio; Tsai, Theodore; Del Giudice, Giuseppe
MF59 is a well-established, safe and potent vaccine adjuvant that has been licensed for more than 13 years for use in an influenza vaccine focused on elderly subjects (Fluad ®®, Novartis, Cambridge, MA, USA). Recently, MF59 was shown to be safe in a seasonal influenza vaccine for young children and was able to increase vaccine efficacy from 43 to 89%. A key and consistent feature of MF59 is the ability of the emulsion to induce fast priming of influenza antigen-specific CD4 + T-cell responses, to induce strong and long-lasting memory T- and B-cell responses and to broaden the immune response beyond the influenza strains actually included in the vaccine. The enhanced breadth of response is valuable in the seasonal setting, but is particularly valuable in a (pre-) pandemic setting, when it is difficult to predict which strain will emerge to cause the pandemic. We have shown that the ability of MF59 to increase the breadth of immune response against influenza vaccines is mainly due to the spreading of the repertoire of the B-cell epitopes recognized on the hemagglutinin and neuraminidase of the influenza virus.